Trace-Level Extraction Behavior of Actinide Elements by Aliphatic Alcohol Extractants in Mineral Acids: Insights into the Trace Solution Chemistry of Protactinium. Issue 6 (18th September 2016) - Knight, Andrew W.; Eitrheim, Eric S.; Nelson, Andrew W.; Peterson, Madeline; McAlister, Daniel; Forbes, Tori Z.; Schultz, Michael K.
ABSTRACT: The extraction of actinide elements thorium, protactinium (Pa), uranium, neptunium, and americium by aliphatic alcohols (1-octanol, 2-ethyl-hexanol, and 2, 6-dimethyl-4-heptanol) was investigated with solvent extraction and extraction chromatographic techniques from hydrochloric and nitric acid solutions. These systems provide the potential for low-cost, high quality methods for the isolation of Pa from complex matrices. Acid dependency experiments demonstrate the selective extraction of protactinium from hydrochloric and nitric acids, relative to the other actinides explored. Experiments were conducted to elucidate the equilibrium chemical stoichiometry of the protactinium complex that underlies this unique extraction behavior. Slope analysis with respect to the alcohol concentration infers a stoichiometric relationship of 2:1 for the alcohol extractant to the protactinium ion. Slope analysis with respect to the chloride ion (when [H + ] = 0.1, 1, and 4 M) suggests that the stoichiometric identity of the protactinium chloro-complexes depends on the [H + ] (0.1 M to 4 M). Extraction of Pa increases as the Pa:Cl ratio increases from 1:2, at low acid concentration, to 1:6 at high acid concentration. With respect to the nitrate ion (when [H + ] = 1 and 4 M), the stoichiometric relationship was determined to be 2:1 nitrate to protactinium throughout the range investigated. The sum of these findings and observations contribute to a deeper understanding of the unique chemistry of protactinium compared to the other members of the actinide group.